2014
DOI: 10.1186/1471-2164-15-496
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of pathogenicity factors of the free-living amoeba Naegleria fowleri

Abstract: BackgroundThe free-living amoeba Naegleria fowleri is the causative agent of the rapidly progressing and typically fatal primary amoebic meningoencephalitis (PAM) in humans. Despite the devastating nature of this disease, which results in > 97% mortality, knowledge of the pathogenic mechanisms of the amoeba is incomplete. This work presents a comparative proteomic approach based on an experimental model in which the pathogenic potential of N. fowleri trophozoites is influenced by the compositions of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 75 publications
5
77
0
Order By: Relevance
“…Amphotericin B acts on target cells by binding to ergosterol present in the cell membrane alter membrane permeability by forming pores and hence cause cell death. However, the use of this drug alone or in combination with other drugs treated not more than a dozen patients successfully while approximately more than 350 cases of PAM have been reported worldwide . The number of patients treated with amphotericin B is 36 while only three (8%) patients survived …”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphotericin B acts on target cells by binding to ergosterol present in the cell membrane alter membrane permeability by forming pores and hence cause cell death. However, the use of this drug alone or in combination with other drugs treated not more than a dozen patients successfully while approximately more than 350 cases of PAM have been reported worldwide . The number of patients treated with amphotericin B is 36 while only three (8%) patients survived …”
Section: Managementmentioning
confidence: 99%
“…However, the use of this drug alone or in combination with other drugs treated not more than a dozen patients successfully while approximately more than 350 cases of PAM have been reported worldwide. 79,80 The number of patients treated with amphotericin B is 36 while only three (8%) patients survived. 21 Several experiments were performed to determine the efficacy of amphotericin in combination with other drugs because of its several side effects.…”
Section: Antimicrobial Agents As Anti-naegleria Drugsmentioning
confidence: 99%
“…Sometimes, a genomic comparison between a pathogenic species and a closely related non-pathogenic species can help identify pathogenicity or virulence factors. The genome of a non-pathogenic Naegleria species, N. gruberi , was sequenced in 2010 and the genome sequence of N. fowleri was reported in 2014 [35, 36]. However, comparison of the two suggest that the N. gruberi genome is too diverse to compare to N. fowleri to identify pathogenicity or virulence factors in the latter ameba.…”
Section: Advanced Molecular Techniquesmentioning
confidence: 99%
“…Comparative studies using transcriptomic and proteomic data from highly and weakly virulent N. fowleri trophozoites have identified about two dozen potential targets that may be directly involved in amebic pathogenicity and virulence [36]. Recently, a matrix-assisted laser-desorption-ionization-time-of-flight (MALDITOF) mass spectrometry approach has been used to identify protein biomarkers for pathogenic N. fowleri using 18 N. fowleri strains (including 14 from PAM cases and 4 from environmental sources) and 6 non-pathogenic Naegleria species: N. gruberi , N. lovaniensis , N. australiensis , N. dunnebackei , N. jadinii , and N. italica [39].…”
Section: Advanced Molecular Techniquesmentioning
confidence: 99%
“…Originally, all Naegleria were grouped in the species N. gruberi, but then an opportunistic human pathogenic species was found and named N. fowleri (Fulton 1970). Studies quickly showed that the genus is extremely diverse (Fulton 1993), a conclusion confirmed by the marked differences in gene sequences and gene order between the genomes of N. gruberi (Fritz-Laylin et al 2010) and N. fowleri (Zysset-Burri et al 2014). Studies by several methods, but mostly using sequences of the ITS1 region of the ribosomal plasmid present in all species, have indicated that there are about 40 species in the genus Naegleria (De Jonckheere 2004, 2008.…”
Section: Closed-tube Barcoding Of Naegleria Could Allow the Identificmentioning
confidence: 99%